Association Between Aneurysmal Hemodynamics and Rupture Risk of Unruptured Intracranial Aneurysms - Tian, Zhongbin; Li, Xifeng; Wang, Chao; Feng, Xin; Sun, Kaijian; Tu, Yi; Su, Hengxian; Yang, Xinjian; Duan, Chuanzhi (Frontiers in Neurology, 2022)
Background Assessing rupture risk in patients with unruptured intracranial aneurysms (UIAs) remains challenging. Hemodynamics plays an important role in the natural history of intracranial aneurysms. This study aimed to compare aneurysmal hemodynamic features between patients with different rupture risk as determined by PHASES score. Methods We retrospectively examined 238 patients who harbored a solitary saccular UIA. Patients were stratified by rupture risk into low-, intermediate-, and high-risk groups according to PHASES score. Flow simulations were performed to compare differences in hemodynamics among the groups. Results Aneurysmal time-averaged wall shear stress (WSSa) and normalized WSS (WSSn) decreased progressively as PHASES score increased. WSSa and WSSn significantly differed among the low-, intermediate-, and high-risk groups (p < 0.001). WSSa was significantly lower in the high-risk group than the low-risk group (p < 0.001) and the intermediate-risk group (p = 0.004). WSSn was also significantly lower in the high-risk group than the low-risk group (p < 0.001) and the intermediate-risk group (p = 0.001). Conclusions Low WSS was significantly associated with higher risk of intracranial aneurysm rupture as determined by PHASES score, indicating that hemodynamics may play an important role in aneurysmal rupture. In the future, a multidimensional rupture risk prediction model that includes hemodynamic parameters should be investigated.